Immunomodulatory mechanisms and therapeutic potential of mesenchymal stem cells - Yang, Guoqiang; Fan, Xuehui; Liu, Yingchun; Jie, Pingping; Mazhar, Maryam; Liu, Yong; Dechsupa, Nathupakorn; Wang, Li (Stem cell reviews and reports, 2023)
Mesenchymal stem cells (MSCs) are regarded as highly promising cells for allogeneic cell therapy, owing to their multipotent nature and ability to display potent and varied functions in different diseases. The functions of MSCs, including native immunomodulation, high self-renewal characteristic, and secretory and trophic properties, can be employed to improve the immune-modulatory functions in diseases. MSCs impact most immune cells by directly contacting and/or secreting positive microenvironmental factors to influence them. Previous studies have reported that the immunomodulatory role of MSCs is basically dependent on their secretion ability from MSCs. This review discusses the immunomodulatory capabilities of MSCs and the promising strategies to successfully improve the potential utilization of MSCs in clinical research.
Online veröffentlicht: 14. April 2023
Gesehen am 14.10.2024